An Activity-Based Probe for Cathepsin K Imaging with Excellent Potency and Selectivity - Lemke, Carina; Benýšek, Jakub; Brajtenbach, Dominik; Breuer, Christian; Jílková, Adéla; Horn, Martin; Buša, Michal; Ulrychová, Lenka; Illies, Annika; Kubatzky, Katharina F; Bartz, Ulrike; Mareš, Michael; et al. (Journal of medicinal chemistry, 2021)
The cysteine protease cathepsin K is a target for the treatment of diseases associated with high bone turnover. Cathepsin K is mainly expressed in osteoclasts and responsible for the destruction of the proteinaceous components of the bone matrix. We designed various fluorescent activity-based probes (ABPs) and their precursors that bind to and inactivate cathepsin K. ABP 25 exhibited extraordinary potency (kinac/Ki = 35,300 M-1s-1) and selectivity for human cathepsin K. Crystal structures of cathepsin K in complex with ABP 25 and its nonfluorescent precursor 21 were determined to characterize the binding mode of this new type of acrylamide-based Michael acceptor with the particular orientation of the dibenzylamine moiety to the primed subsite region. The cyanine-5 containing probe 25 allowed for sensitive detection of cathepsin K, selective visualization in complex proteomes, and live cell imaging of a human osteosarcoma cell line, underlining its applicability in a pathophysiological environment.
Keywords: kathepsin K; Protein Binding; Fluorescent Dyes; Cathepsin K; Cell Line, Tumor; konfokální mikroskopie; fluorescenční mikroskopie; Acrylamides; racionální návrh léčiv; inhibitory cysteinových proteinas; Microscopy, Confocal; vazba proteinů; lidé; Microscopy, Fluorescence; Catalytic Domain; Humans; fluorescenční barviva; akrylamidy; Drug Design; Cysteine Proteinase Inhibitors; nádorové buněčné linie; katalytická doména